Explanation:
It is given that,
Initially, the jogger is at rest u₁ = 0
He accelerates from rest to 4.86 m, v₁ = 4.86 m
Time, t₁ = 2.43 s
A car accelerates from u₂ = 20.6 to v₂ = 32.7 m/s in t₂ = 2.43 s
(a) Acceleration of the jogger :
[tex]a=\dfrac{v-u}{t}[/tex]
[tex]a=\dfrac{4.86\ m/s-0}{2.43\ s}[/tex]
a₁ = 2 m/s²
(b) Acceleration of the car,
[tex]a=\dfrac{v-u}{t}[/tex]
[tex]a=\dfrac{32.7\ m/s-20.6\ m/s}{2.43\ s}[/tex]
a₂ = 4.97 m/s²
(c) Distance covered by the car,
[tex]d_1=u_1t_1+\dfrac{1}{2}a_1t_1^2[/tex]
[tex]d_1=0+\dfrac{1}{2}\times 2\times (2.43)^2[/tex]
d₁ = 5.904 m
Distance covered by the jogger,
[tex]d_2=u_2t_2+\dfrac{1}{2}a_2t_2^2[/tex]
[tex]d_2=20.6\times 2.43+\dfrac{1}{2}\times 4.97\times (2.43)^2[/tex]
d₂ = 64.73 m
The car further travel a distance of, d = 64.73 m - 5.904 m = 58.826 m
Hence, this is the required solution.